Effects of extremely low frequency electromagnetic fields on biological systems - (:unkn) unknown (My University, 2003)
The effects of Extremely Low Frequency Electromagnetic Fields (3-300kHz) on living beings has been investigated in the last decades since it was demonstrated that there was an increased incidence of childhood leukemia among residences near power lines. Epidemiological and laboratory studies have increased in number since then, however, a definitive cause-effect relationship has not been found yet. The most important reason is a lack of mechanism for the interaction of these non-ionizing, non-thermal electromagnetic fields with biological systems. This overview aims to summarize epidemiological and laboratory in vivo and in vitro studies made in this field.
Keywords: ELF-EMF; Epidemiological; Non-ionizing radiation; Signal transduction